Analysis of diarylmethylamine compounds using electrospray mass spectrometry: formation mechanisms of radical ions and dehydro cations. Issue 23 (14th October 2015) - Cai, Tian; Xu, Xiao-Ying; Wu, Zhi-Jun
Abstract : Unexpected ions, M + ˙ and [M − H] +, were detected in the analysis of diarylmethylamine compounds using ESI-MS and the rules for the ratio change of I [M] + ˙ / I [M−H] + were explicated. Abstract : A series of diarylmethylamine compounds were analyzed using electrospray ionization quadrupole time-of-flight mass spectrometry (ESI-QTOF-MS). [M] + ˙ and [M − H] + were both observed, but showed different abundances. A possible mechanism for the formation of [M] + ˙ and [M − H] + was proposed to explicate the rule for the ratio change of I [M] + ˙ / I [M−H] + . The [M] + ˙ has two structures, which can interconvert into each other in the gas phase. The substituted groups on the benzene rings play a crucial role in the transfer between the two structures. Electron withdrawing groups can prevent the formation of carbocations, thus nitro-containing diarylmethylamines remained mainly as structure I and were detected as [M] + ˙. On the contrary, electron donating groups help to stabilize carbocations. This makes structure I transfer to structure II, and structure II prefers to further generate [M − H] + by loss of an H radical. Nuclear magnetic resonance and D-labelled MS experiments indicate that the 1-C–H bond has strong activity.